2020
DOI: 10.1002/mus.27070
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria for idiopathic small fiber neuropathy: A systematic review

Abstract: Idiopathic small fiber neuropathy (iSFN) lacks broadly accepted diagnostic criteria, which hinders its timely diagnosis and treatment. A systematic literature review was performed to assess the published screening and diagnostic criteria for iSFN, excluding studies where SFN was of well‐established etiology. Eighty‐four clinical studies and seven guideline/review publications were included in this systematic review. Substantial heterogeneity existed in iSFN diagnostic criteria. The most common set of criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…The patient did not fulfill the current criteria of SFN based on the IENFD and/or quantitative sensory testing (QST), 2 but those criteria are controversial. 4 Considering the clinical signs and symptoms, the normal EDX, and the absent LEPs, we believe the clinical painful picture was consistent with small nerve fiber involvement. In this context, the presence of anti-CASPR2 immunostaining on Aδ-fibers juxtaparanodes and C-fibers was meaningful.…”
Section: Discussionmentioning
confidence: 73%
“…The patient did not fulfill the current criteria of SFN based on the IENFD and/or quantitative sensory testing (QST), 2 but those criteria are controversial. 4 Considering the clinical signs and symptoms, the normal EDX, and the absent LEPs, we believe the clinical painful picture was consistent with small nerve fiber involvement. In this context, the presence of anti-CASPR2 immunostaining on Aδ-fibers juxtaparanodes and C-fibers was meaningful.…”
Section: Discussionmentioning
confidence: 73%
“…Small fiber neuropathies (SFNs) are disorders of unmyelinated C-fibers and poorly myelinated A-delta fibers, which induce pruritus and other cutaneous paresthesia [15][16][17]. A recent systematic literature review showed an unmet need of broadly accepted diagnostic criteria, although the most common set of mandatory criteria to diagnose were sensory symptoms (60% of studies), pain (19% of studies), small fiber signs (20% of studies), absence of large fiber signs (62% of studies), reduced intra-epidermal nerve fiber density (IENFD) (38% of studies), and autonomic symptoms (1% of studies) [18]. Nonetheless, the joint task force of the European Federation of Neurological Societies (EFNS) and the Peripheral Nerve Society (PNS) agreed to consider that skin biopsy with the quantification of the IENFD, using generally agreed upon counting rules, is a reliable and efficient technique to assess the diagnosis of SFN [19].…”
Section: Arguments For Sensitive Skins As Small-fiber Neuropathiesmentioning
confidence: 99%
“…Immunohistochemistry or immunofluorescence with polyclonal anti-PGP 9.5 must be performed in a laboratory with experience in the interpretation of this diagnosis. Normative reference values of intraepidermal nerve fibre depend on age and gender [21] but are not used in all the studies [22]. Moreover, a recent small-scale study showed that the IENFD at the distal leg appeared influenced by the ethnicity : IENFD is lower in Chinese Americans than in non-Chinese Americans [23], but normative data depending on ethnicity are not available.…”
Section: Pathophysiology Of Small Fibre Neuropathymentioning
confidence: 99%